الاغتيال السياسي: مفهومه، تكييفه، نماذجه، وتجريمه في الفقه والقانون (Al-Qamar, 2024)
Under Islamic Sharia, the crime of political assassination is, indeed, a political crime as a criminal offense and is considered a non-political crime as a penalty or punishment. It is the physical elimination of a political figure for a political purpose. With no doubt, by killing the ruler or President of a country, the regime may fall in some cases. It is a political crime in this sense, and it is a non-political crime as a punishment or penalty in accordance with Islamic Sharia, International and national law. Because the perpetrator of the crime of political assassination is punished with the most severe punishment, even death by hanging, unlike the general political crime. The crime of political assassination is as old as politics itself. Since the state existed, politics and political assassination have also been existed with state. Even during the best Islamic centuries (i.e Khilfa Al-Rashida period) the Khalifa (rulers) were assassinated by the opponents. In this article, we will endeavor to discuss the provisions of political assassination from Islamic Sharia perspective, and will make its comparison with both International and Afghan laws as well.
Keywords: Political assassination; Islamic law; international criminal law